Peran Humas dalam Membangun Komunikasi Internal dan Eksternal CV Rinjani Mitra Jaya - Noviani, Ida Ayu; Nyoman Sutriani, Ida Ayu (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
This study examines the role of public relations in creating both internal and external communication at CV Rinjani Mitra Jaya, a growing distribution company. Public relations plays a crucial role as a liaison in transferring information from employees to management, while simultaneously strengthening the company's relationships with external parties, such as principals, customers, business partners, the media, and the government. The methodology used in this study was descriptive qualitative, with data collection through observation, in-depth interviews, and documentation. Data were analyzed through data reduction, presentation, and conclusion drawing to provide a clear understanding of the phenomenon under study. The findings of this study confirm that human resources play a significant role in maintaining smooth internal communication, both in conveying policies and creating two-way communication channels between employees and management. Furthermore, public relations also plays a crucial role in external communication by ensuring harmonious relationships with principals and maintaining a positive company image. Consequently, the presence of human resources has the potential to increase trust, strengthen reputation, and support the company's competitiveness in facing business competition. This research provides a practical contribution to the development of organizational communication strategies, particularly in managing the role of public relations in distribution companies.